Discounting Restricted Securities - Umar, Tarik; Yimfor, Emmanuel; Zufarov, Rustam (Journal of Financial and Quantitative Analysis, 2023)
We examine the costs of trading restrictions by exploiting an SEC rule change eliminating an approximately 80-day restriction period in private placements for small issuers. Using a difference-in-differences specification, we find that the restriction is binding, as dollar volume increases 19 percentage points vis-à-vis proceeds, and costly, as offering discounts fall by 8 percentage points. Discounts fall more for issuers with higher information asymmetry or longer restriction periods. We account for endogenous responses to the rule change. Overall, our findings suggest that trading restrictions are costly and have large effects on firms’ cost of capital.